Experimental and simulation-based investigation of He, Ne and Ar irradiation of polymers for ion microscopy - Rzeznik, Lukasz; Fleming, Yves; Wirtz, Tom; Philipp, Patrick (Beilstein Journal of Nanotechnology, 2016)
Secondary ion mass spectrometry (SIMS) on the helium ion microscope (HIM) promises higher lateral resolution than on classical SIMS instruments. However, full advantage of this new technique can only be obtained when the interaction of He+ or Ne+ primary ions with the sample is fully controlled. In this work we investigate how He+ and Ne+ bombardment influences roughness formation and preferential sputtering for polymer samples and how they compare to Ar+ primary ions used in classical SIMS by combining experimental techniques with Molecular Dynamics (MD) simulations and SD_TRIM_SP modelling. The results show that diffusion coefficients for He, Ne and Ar in polymers are sufficiently high to prevent any accumulation of rare gas atoms in the polymers which could lead to some swelling and bubble formation. Roughness formation was also not observed. Preferential sputtering is more of a problem, with enrichment of carbon up to surface concentrations above 80%. In general, the preferential sputtering is largely depending on the primary ion species and the impact energies. For He+ bombardment, it is more of an issue for low keV impact energies and for the heavier primary ion species the preferential sputtering is sample dependent. For He+ steady state conditions are reached for fluences much higher than 1018 ions/cm2. For Ne+ and Ar+, the transient regime extends up to fluences of 1017–1018 ions/cm2. Hence, preferential sputtering needs to be taken into account when interpreting images recorded under He+ or Ne+ bombardment on the HIM.
Keywords: Helium ion microscopy; irradiation; polymers; preferential sputtering; secondary ion mass spectrometry; simulations

(untitled) - Levi-Setti, R.; Wang, Y. L.; Crow, G. (Appl. Surf. Sci., 1986)

(untitled) - Wirtz, T.; Vanhove, N.; Pillatsch, L.; Dowsett, D.; Sijbrandij, S.; Notte, J. (Appl. Phys. Lett., 2012)

(untitled) - Wirtz, T.; Philipp, P.; Audinot, J.-N.; Dowsett, D.; Eswara Moorthy, S. (Nanotechnology, 2015)

(untitled) - Scipioni, L.; Sanford, C. A.; Notte, J.; Thompson, B.; Mcvey, S. (J. Vac. Sci. Technol., B, 2009)

(untitled) - Strick, R.; Strissel, P. L.; Gavrilov, K.; Levi-Setti, R. (J. Cell Biol., 2001)

(untitled) - Audinot, J.-N.; Schneider, S.; Yegles, M.; Hallégot, P.; Wennig, R.; Migeon, H.-N. (Appl. Surf. Sci., 2004)

(untitled) - Hallégot, P.; Audinot, J.-N.; Migeon, H.-N. (Appl. Surf. Sci., 2006)

(untitled) - Galle, P.; Levi-Setti, R.; Lamperti, A.; Bourahla, K.; Escaig, F. (Appl. Surf. Sci., 2004)

(untitled) - Eybe, T.; Audinot, J. N.; Bohn, T.; Guignard, C.; Migeon, H. N.; Hoffmann, L. (J. Appl. Microbiol., 2008)

(untitled) - Smart, K. E.; Kilburn, M. R.; Salter, C. J.; Smith, J. A. C.; Grovenor, C. R. M. (Int. J. Mass Spectrom., 2007)

(untitled) - Moore, K. L.; Schröder, M.; Lombi, E.; Zhao, F.-J.; McGrath, S. P.; Hawkesford, M. J.; Shewry, P. R.; Grovenor, C. R. M. (New Phytol., 2010)

(untitled) - Colla, T. J.; Urbassek, H. M.; Nordlund, K.; Averback, R. S. (Phys. Rev. B, 2001)

(untitled) - Anders, C.; Urbassek, H. M. (J. Phys. Chem. C, 2010)

(untitled) - Philipp, P.; Briquet, L.; Wirtz, T.; Kieffer, J. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2011)

(untitled) - Barry, P. R.; Philipp, P.; Wirtz, T.; Kieffer, J. (J. Mass Spectrom., 2014)

(untitled) - Garrison, B. J.; Postawa, Z. (Mass Spectrom. Rev., 2008)

(untitled) - Garrison, B. J. (J. Am. Chem. Soc., 1980)

(untitled) - Taylor, R. S.; Garrison, B. J. (J. Am. Chem. Soc., 1994)

(untitled) - Beardmore, K.; Smith, R. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1995)

(untitled) - Hnatowicz, V.; Peřina, V.; Macková, A.; Švorčı́k, V.; Rybka, V.; Fink, D.; Heitz, J. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2001)

(untitled) - Delcorte, A.; Garrison, B. J. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2001)

(untitled) - Delcorte, A.; Bertrand, P.; Garrison, B. J. (J. Phys. Chem. B, 2001)

(untitled) - Tan, S.; Livengood, R.; Shima, D.; Notte, J.; McVey, S. (J. Vac. Sci. Technol., B, 2010)

(untitled) - Livengood, R.; Tan, S.; Greenzweig, Y.; Notte, J.; McVey, S. (J. Vac. Sci. Technol., B, 2009)

SDTrimSP Version 5.00 (IPP 12/8) - Mutzke, A.; Schneider, R.; Eckstein, W.; Dohmen, R. (2011)

(untitled) - Mansilla, C.; Philipp, P.; Wirtz, T. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2011)

(untitled) - Mansilla, C.; Philipp, P.; Wirtz, T. (Surf. Interface Anal., 2013)

(untitled) - Barbot, J.-F.; Pailloux, F.; David, M.-L.; Pizzagalli, L.; Oliviero, E.; Lucas, G. (J. Appl. Phys., 2008)

(untitled) - Frabboni, S.; Corni, F.; Nobili, C.; Tonini, R.; Ottaviani, G. (Phys. Rev. B, 2004)

(untitled) - Lucas, G.; Schäublin, R. (J. Nucl. Mater., 2009)

(untitled) - Kawakami, T.; Tokunaga, K.; Yoshida, N. (J. Nucl. Mater., 2007)

(untitled) - Yoshida, N.; Iwakiri, H.; Tokunaga, K.; Baba, T. (J. Nucl. Mater., 2005)

Atomistic Modeling of Physical Properties - Gusev, A. A.; Müller-Plathe, F.; van Gunsteren, W. F.; Suter, U. W. (Dynamics of small molecules in bulk polymers, 1994)

(untitled) - Kucukpinar, E.; Doruker, P. (Polymer, 2003)

(untitled) - Mozaffari, F.; Eslami, H.; Moghadasi, J. (Polymer, 2010)

(untitled) - Jung, P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1994)

(untitled) - Macdonald, R. W.; Huang, R. Y. M. (J. Appl. Polym. Sci., 1981)

(untitled) - Bixler, H. J.; Michaels, A. S.; Salame, M. (J. Polym. Sci., Part A: Gen. Pap., 1963)

(untitled) - Flaconneche, B.; Martin, J.; Klopffer, M. H. (Oil Gas Sci. Technol., 2001)

Diffusion in polymer science - Crank, J.; Park, G. S. (Academic Press, 1975)

Encyclopedia of polymer science and engineering - Mark, H. F. (Wiley-VCH, 1989)

(untitled) - Min, K. E.; Paul, D. R. (J. Polym. Sci., Part B: Polym. Phys., 1988)

(untitled) - Reznickova, A.; Kolska, Z.; Hnatowicz, V.; Svorcik, V. (J. Nanopart. Res., 2011)

(untitled) - Turgut, C.; Sinha, G.; Lahtinen, J.; Nordlund, K.; Belmahi, M.; Philipp, P. (J. Mass Spectrom.)

(untitled) - Turgut, C.; Wirtz, T.; Belmahi, M.; Philipp, P. (Surf. Interface Anal., 2014)

(untitled) - Zekonyte, J.; Erichsen, J.; Zaporojtchenko, V.; Faupel, F. (Surf. Sci., 2003)

(untitled) - Calcagno, L.; Compagnini, G.; Foti, G. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1992)

Secondary Ion Mass Spectrometry SIMS V - Migeon, H. N.; Le Pipec, C.; Le Goux, J. J. (A New SIMS Instrument: The Cameca IMS 4F, 1985)

(untitled) - Lejeune, C. (Nucl. Instrum. Methods, 1974)

(untitled) - Pillatsch, L.; Wirtz, T. (Surf. Interface Anal., 2012)

Agilent Technologies (2008)

(untitled) - Necas, D.; Klapetek, P. (2010)

Polymer Modeler, Version 3.17 (2015)

(untitled) - Plimpton, S. (J. Comput. Phys., 1995)

(untitled) - Mayo, S. L.; Olafson, B. D.; Goddard, W. A. (J. Phys. Chem., 1990)

(untitled) - Pricl, S.; Fermeglia, M. (Chem. Eng. Commun., 2003)

(untitled) - June, R. L.; Bell, A. T.; Theodorou, D. N. (J. Phys. Chem., 1991)

Properties of Polymers - van Krevelen, D. W.; te Nijenhuis, K. (Elsevier Science, 2009)

(untitled) - Andersson, T.; Stålbom, B.; Wesslén, B. (J. Appl. Polym. Sci., 2004)

(untitled) - Sato, H.; Shimoyama, M.; Kamiya, T.; Amari, T.; Šašic, S.; Ninomiya, T.; Siesler, H. W.; Ozaki, Y. (J. Appl. Polym. Sci., 2002)

(untitled) - Wang, T.; Heermann, D. W.; Heilig, J.-C. (Macromol. Theory Simul., 2000)

(untitled) - Tsai, B. K.; Allen, D. W.; Hanssen, L. M.; Wilthan, B.; Zeng, J. (Proc. SPIE, 2008)

(untitled) - Hess, B.; Kutzner, C.; van der Spoel, D.; Lindahl, E. (J. Chem. Theory Comput., 2008)

(untitled) - Jorgensen, W. L.; Maxwell, D. S.; Tirado-Rives, J. (J. Am. Chem. Soc., 1996)

(untitled) - Berendsen, H. J. C.; Postma, J. P. M.; Van Gunsteren, W. F.; Dinola, A.; Haak, J. R. (J. Chem. Phys., 1984)

(untitled) - Biersack, J. P.; Haggmark, L. G. (Nucl. Instrum. Methods, 1980)

(untitled) - Eckstein, W.; Möller, W. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1985)

(untitled) - Möller, W.; Eckstein, W. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1984)

(untitled) - Möller, W.; Eckstein, W.; Biersack, J. P. (Comput. Phys. Commun., 1988)

(untitled) - Mutzke, A.; Eckstein, W. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2008)